The response of benthic foraminifera to pollution and environmental stress in Ria de Aveiro (N Portugal) - Martins, V. (2011)
This work evaluates the quality of the sediment in Ria de Aveiro, a coastal lagoon located at N of Portugal that is under strong anthropic influence, and the effects of the contamination on benthic foraminifera. The initial approach for measuring pollution was done through the load pollution index (LPI), based on As, Cd, Cr, Cu, Ni, Pb and Zn concentrations, and determined by total digestion of the sediments (TDS). This information was complemented by conducting a metal fractionation technique (sequential chemical extraction - SCE) in some of the most contaminated samples in order to define the relevance of different metal bearing- phases (exchangeable cations adsorbed by clay and co-precipitated with carbonates, absorbed by organic matter and retained in the mineralogical phase) and to evaluate the toxic heavy metal availability. Multivariable statistical analyses were carried out taking into consideration the geochemical results, as well as the biotic (percentage of species/groups of species; foraminifer abundance and diversity) and abiotic variables, such as sediment content in mud, total organic carbon (TOC) and Eh. SCE results show that most of the element concentration in the sediments is retained in the resistant mineralogical phase. However, the higher bioavailability of some toxic elements, such as As, Cd, Cu, Hg, Ni, Pb and Zn, found in Laranjo Bay, Aveiro City, Aveiro Harbours and Espinheiro Channel, have a generic negative impact on benthic foraminifera of the Aveiro lagoon. Differential sensitivity of benthic foraminifera to high concentrations of heavy metals may exist. quinqueloculina seminulum, for instance, seems to be more tolerant to higher bioavailable concentrations of Pb and Cu than Ammonia tepida or Haynesina germanica. Both species were previously considered to be the most heavy metal-tolerant foraminifer species. This study confirmed the use of benthic foraminifera as an important tool for the evaluation of the environmental quality of an ecosystem and for monitoring and restoring it.